Раскопки курганов у с. Николаевка Петропавловского р-на Днепропетровской обл. - Ромашко, В.А.; Тесленко, Д.Л.; Фещенко, Е.Л. (Археологічні дослідження в Україні, 2009)
The results of excavations of three barrows in the Samara River upper region near Mykolaivka village of Petropavlivka Region in Dniptopetrovsk Oblast are published. The burials of the Copper Age, of the Bronze Age Steppe cultures: Yamna, Catacomb, Multiraized Border Pottery, and Zrubna cultures, and a Mediaeval Epoch tomb were discovered.